2016
DOI: 10.1017/cjn.2016.284
|View full text |Cite
|
Sign up to set email alerts
|

Panel of Oxidative Stress and Inflammatory Biomarkers in ALS: A Pilot Study

Abstract: We confirmed the systemic alteration of both the redox and the inflammation status in ALS patients, and we observed a link with some clinical parameters. These promising results encourage us to pursue this study with collection of combined oxidative stress and inflammatory markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(92 citation statements)
references
References 33 publications
3
88
0
1
Order By: Relevance
“…Several studies have showed the usefulness of oxidative stress biomarkers that were measured in the blood, plasma, serum, urine, or CSF in the diagnosis of NDDs [77,78,[111][112][113][114][115]. However, so far, scarce literature data describe their diagnostic value in saliva.…”
Section: Summary and Perspectivementioning
confidence: 99%
“…Several studies have showed the usefulness of oxidative stress biomarkers that were measured in the blood, plasma, serum, urine, or CSF in the diagnosis of NDDs [77,78,[111][112][113][114][115]. However, so far, scarce literature data describe their diagnostic value in saliva.…”
Section: Summary and Perspectivementioning
confidence: 99%
“…Markers for OS have been determined in the cerebrospinal fluid (CSF), tissues, blood and urine of patients with ALS (Blasco et al, 2017). After postmortem analysis of neuronal tissues in sALS and fALS patients, an increase of OS biomarkers was noted in proteins, lipids and DNA (Beal, 2002;Agar and Durham, 2003;Kim et al, 2003;Turner et al, 2013;Bozzo et al, 2016).…”
Section: High Levels Of Certain Types Of Ros (H 2 O 2 and O •−mentioning
confidence: 99%
“…The evaluation of GPx activity, glutathione reductase (GR), SOD, total serum antioxidant status (TAS), MDA and 8-OHdG in ALS patients, found a significant decrease in TAS levels and an increase of 8-OHdG and MDA levels, together with significantly higher oxidized/reduced glutathione (GSSG/GSH) ratio and IL-6 and IL-8 (Blasco et al, 2017).…”
Section: High Levels Of Certain Types Of Ros (H 2 O 2 and O •−mentioning
confidence: 99%
“…Mutant SOD1 leads to aggregation in motor neurons within the CNS [193]. Other causes include oxidative stress, neuroin lammation, glutamate excitotoxicity, changes in neuro ilaments, mitochondrial degeneration and damage, protein aggregation, apoptosis, and de iciencies in factors related to growth [46,[203][204][205]. Owing to the accumulation of dysfunctional mitochondria within the motor neurons impacted by the sporadic and genetic types of ALS, there is a clear indication that a failure to maintain healthy mitochondria exacerbates ALS [206,207].…”
Section: Als and Oxidative Stressmentioning
confidence: 99%